Aviation infrastructure performance : a study in comparative political economy - Winston, Clifford, 1952-; Rus, Ginés de (Brookings Institution Press, 2008)
"International transportation experts compare and contrast how different nations have managed their airports and air traffic control systems to address congestion and delays, carrier competition, and air travel safety and how well they are meeting the needs of their people"--Provided by publisher.